Life-Cycle Cost Model and Design Optimization of Base-Isolated Building Structures - Mitropoulou, Chara Ch.; Lagaros, Nikos D. (Frontiers in Built Environment, 2016)
Design of economic structures adequately resistant to withstand during their service life, without catastrophic failures, all possible loading conditions and to absorb the induced seismic energy in a controlled fashion, has been the subject of intensive research so far. Modern buildings usually contain extremely sensitive and costly equipment that are vital in business, commerce, education and/or health care. The building contents frequently are more valuable than the buildings them-selves. Furthermore, hospitals, communication and emergency centres, police and fire stations must be operational when needed most: immediately after an earthquake. Conventional con-struction can cause very high floor accelerations in stiff buildings and large interstorey drifts in flexible structures. These two factors cause difficulties in insuring the safety of both building and its contents. For this reason base-isolated structures are considered as an efficient alternative design practice to the conventional fixed-base one. In this study a systematic assessment of op-timized fixed and base-isolated reinforced concrete buildings is presented in terms of their initial and total cost taking into account the life-cycle cost of the structures.